PENGARUH pH DAN DOSIS KOAGULAN EKSTRAK BIJI KELOR DALAM KOAGULASI TERHADAP PENGURANGAN KEKERUHAN LIMBAH CAIR - Herawati, Astrid; Asti, Riistika; Ismuyanto, Bambang; Nanda, Julia; Hidayati, A.S. Dwi Saptati N. (Jurnal Rekayasa Bahan Alam dan Energi Berkelanjutan, 2017)
The presence of suspended and colloidal particles in water can cause turbidity. To reduce the turbidity, coagulation–flocculation process is commonly used. In this process, the colloidal particle is converted into flocs which easily separated from water with the aid of coagulant. One of the natural coagulants that have been studied as water purifier is Moringa oleifera seeds. This research aims to reduce turbidity of kaolin synthetic wastewater through coagulation–flocculation process using Moringa oleifera seeds that have been extracted with NaCl 1 M. The variables used in this study were wastewater pH (3, 6, 10, and 12) and coagulant dosage (0, 1, 2, 3, 4, and 5 mL/L). Coagulation-flocculation was taken place in Jar Test with rapid stirring 150 rpm in 2 minutes, followed by slow stirring 30 rpm in 30 minutes, and sedimentation for 30 minutes. Then, the water was analyzed using Turbidimeter. The results showed that coagulant dosage and pH affected the effectiveness of coagulation in decreasing turbidity. The optimum dosage of extracted Moringa oleifera seeds coagulant in coagulation of kaolin synthetic wastewater at pH 3, 6, 10, and 12 were 2 ml/L, 3ml/L, 2 ml/L, and 4 ml/L, respectively.